Negative Representation of Indonesian Female Workers in Hong Kong in Two Articles of South China Morning Post - Antya Catra Denira; Eva Tuckyta Sari Sujatna; Eko Wahyu Koeshandoyo Putro (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
This research is entitled “Negative Representation of Indonesian Female Workers in Hong Kong in Two Articles of South China Morning Post.” This research aims to analyze the elements used by South China Morning Post, a Hong Kong daily, in representing Indonesian female workers negatively on micro level in the macrostructure, superstructure, and microstructure and to describe the negative representations attached to Indonesian female workers. The objects used in this research are two articles related to Indonesian female workers abuse case in Hong Kong from the news media South China Morning Post published on February 2015. This research is a descriptive-qualitative research using critical discourse analysis method of Teun A. van Dijk, which focuses on micro-level analysis. The result of this research shows that Indonesian female workers are represented negatively in macrostructure through the discourse elements of headline and lead, in superstructure through the discourse elements of verbal reactions, main events, and background, and in microstructure through the discourse elements of level of specificity and degree of completeness, implications, presuppositions, and lexical style. They are represented as less educated, weak, and labile figures in the two articles of South China Morning Post. Keywords: critical discourse analysis, negative representation, Indonesian female workers, news media